The genome landscape of the Xinglong buffalo - Yuan Chai; Shiyuan Li; Hui Wu; Yong Meng; Yujing Fu; Hong Li; Guansheng Wu; Junming Jiang; Taoyu Chen; Yuqing Jiao; Qiaoling Chen; Li Du; et al. (BMC Genomics)
Abstract Background Xinglong buffalo, as an indigenous breed in Hainan province of China, possesses characteristics such as high humidity tolerance, disease resistance and high reproductive capacity. Combined with whole genome sequencing technology, comprehensive investigation can be undertaken to elucidate the genomic characteristics, functions and genetic variation of Xinglong buffalo population. Results Xinglong buffalo has the highest genetic diversity, lowest runs of homozygosity average length, and fasted decay of linkage disequilibrium in our study population. Phylogenetic tree results revealed that Xinglong buffalo was gathered together with Fuzhong buffalo firstly. The population genetic structure analysis indicates that at K = 3, the Xinglong buffalo for the first time showed a distinct ancestral origin from other water buffalo. Furthermore, compared to different populations, candidate genes displaying significantly distinct patterns of single nucleotide polymorphisms (SNPs) (e.g., RYR2, COX15, PCDH9, DTWD2, FCRL5) distribution have been identified in the Xinglong buffalo. Conclusions Based on the whole genome sequencing data, this study identified a substantial number of SNPs and assessed the genetic diversity and selection signatures within the Xinglong buffalo population. These results contribute to understanding the genomic characteristics of Xinglong buffalo and their genetic evolutionary status. However, the practical significance of these signatures for genetic enhancement still requires confirmation through additional samples and further experimental validation.